CÁC HỢP CHẤT DIHYDROFLAVONOL GLYCOSIT VÀ APORPHIN ALKALOIT TỪ CÂY LÃNH CÔNG GÂN HOE - Thắng, Lê Quốc; Thuỷ, Trịnh Thị; Sung, Trần Văn (Vietnam Journal of Chemistry, 2012)
Chemical investigation of Fissistigma rufinerve (Hook. f. & Thoms.) Merr. growing in Hoa Binh province, Vietnam led to the isolation of two dihydroflavonol glycosides named astilbin [(2R,3R)-3’,4’,5,7-tetrahydroxydihydroflavonol 3b-O-a-L-rhamnopyranoside], engeletin [(2R,3R)-4’,5,7-trihydroxydihydroflavonol 3b-O-a-L-rhamnopyranoside], and 8-hydroxy-9-methoxy-1,2-methylenedioxyaporphine. Their structures were determined on the basis of MS, NMR spectra and comparison with reported data. Key words: Fissistigma rufinerve, astilbin, engeletin, aporphine.